Intervención de enfermería y su relación con el manejo del dolor en pacientes post quirúrgicos adulto mayor del Hospital General Guasmo Sur durante el periodo junio-octubre 2023 - Medrano Quille, Tania Elizabeth (2023)
The present investigative work is directed to the elderly adult patients who are admitted to the General Hospital Guamo Sur undergoing their hospitalization in the post-operative center with a clinical picture characterized by hypogastric pain that later depending on their surgical intervention. Pain is one of the main conditions presented in older adult patients, and taking into account the different methods of assessing the level of pain, the Eva scale is taken into account, which serves to accurately determine its intensity. and the methods necessary to reduce the intensity, seeking to safeguard the integrity of the patient and seek optimal and quality care for the patient's health. Pain control is essential to improve quality of life. Pain prevents people from doing activities they enjoy. This can keep you from talking and spending time with other people. It affects mood and thinking skills. Also, the pain can make other symptoms worse, making it difficult to eat and sleep. Pain causes pain and suffering to patients and their loved ones. It also increases blood pressure, heart rate and can negatively affect rehabilitation. Control pain can help relieve pain.